2020
DOI: 10.1002/ps.5915
|View full text |Cite
|
Sign up to set email alerts
|

Structure dynamics reveal key residues essential for the sense of 1‐dodecanol by Cydia pomonella pheromone binding protein 2 (CpomPBP2)

Abstract: BACKGROUND: Cydia pomonella, a worldwide quarantine fruit pest, causes great damage to fruit production every year. Sex pheromone-mediated control of C. pomonella has been widely used. As an indispensable ingredient of commercial sex attractants, 1-dodecanol (Dod) works to synergize the effect of codlemone in attracting male moths of C. pomonella. The interactions between Dod and its transporter protein, C. pomonella pheromone-binding protein 2 (CpomPBP2), provide inspiration for chemical optimizations to impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 50 publications
1
23
0
Order By: Relevance
“…Our results revealed that M39A, V68A, W106A, Q107A, and Y114A mutant proteins lost their ability to bind the ligands, suggesting that these residues may be involved in the binding affinity of AlepOBP6 to distinct ligands (key residues of Z 7‐12:Ac: W106 and Y114; Z 9‐14:Ac: V68, W106, and Y114; n ‐nonane and 1‐octen‐3‐ol: M39; (−)‐limonene, n‐nonane, benzaldehyde, decanal, 1‐octen‐3‐ol: Q107; Z 9‐14:Ac, α‐pinene, myrcene, 2‐hexanone, 2‐heptanone, 6‐methyl‐5‐hepten‐2‐one: V68 and Y114). Some studies have confirmed that the mutation of putatively crucial residues to alanine leads to a loss or decrease in the binding ability of OBPs to sex pheromones and host volatiles in other insects, 52,60,61,63–65 and this corresponds with our results. However, we also found no significant difference in the binding affinity of three ligands, (−)‐limonene, benzaldehyde and decanal, between M39A mutant and wild‐type AlepOBP6, which may be due to the bioinformatics prediction not being able to fully simulate the complex internal environment of insects.…”
Section: Discussionsupporting
confidence: 92%
“…Our results revealed that M39A, V68A, W106A, Q107A, and Y114A mutant proteins lost their ability to bind the ligands, suggesting that these residues may be involved in the binding affinity of AlepOBP6 to distinct ligands (key residues of Z 7‐12:Ac: W106 and Y114; Z 9‐14:Ac: V68, W106, and Y114; n ‐nonane and 1‐octen‐3‐ol: M39; (−)‐limonene, n‐nonane, benzaldehyde, decanal, 1‐octen‐3‐ol: Q107; Z 9‐14:Ac, α‐pinene, myrcene, 2‐hexanone, 2‐heptanone, 6‐methyl‐5‐hepten‐2‐one: V68 and Y114). Some studies have confirmed that the mutation of putatively crucial residues to alanine leads to a loss or decrease in the binding ability of OBPs to sex pheromones and host volatiles in other insects, 52,60,61,63–65 and this corresponds with our results. However, we also found no significant difference in the binding affinity of three ligands, (−)‐limonene, benzaldehyde and decanal, between M39A mutant and wild‐type AlepOBP6, which may be due to the bioinformatics prediction not being able to fully simulate the complex internal environment of insects.…”
Section: Discussionsupporting
confidence: 92%
“…Combined CAS and site‐directed mutagenesis has proven effective and reliable in determining the hot‐spots involved in protein‐ligand interaction 33, 36,41,58 . In the present research, seven residues (Leu7, Phe11, Phe35, Trp36, Leu89, Ile93, and Phe116) in total were selected for CAS.…”
Section: Resultsmentioning
confidence: 99%
“…3.4 Hot-spots determination validated the interaction enhancement mediated by the C10═C11 in cod Combined CAS and site-directed mutagenesis has proven effective and reliable in determining the hot-spots involved in protein-ligand interaction. 33,36,41,58 In the present research, seven residues (Leu7, Phe11, Phe35, Trp36, Leu89, Ile93, and Phe116) in total were selected for CAS. The Trp36 was chosen for its centroid role in the binding pocket of GmolPBP2, 36 other residues were chosen for their high energy contributions (≥−1.00 kcal mol −1 ) in the two complexes.…”
Section: Binding Mode Analysis Identified the Key Role Of C10═c11 In ...mentioning
confidence: 99%
“…54 In another study, adding a hydrophilic group to a particular position of 1-dodecanol could facilitate its interaction with Cydia pomonella pheromone binding protein 2, thus providing a foundation for development of biologically more active compounds. 55 Similarly, based on analyses of structural dynamics in our study, it is likely to enhance hydrogen bonding with Trp106 through adding hydrogen bond acceptor groups to geranyl formate [e.g., addition of -OH gives (E)-3,-7-dimethylocta-2,6-dien-1-yl hydrogen carbonate (Supporting Information, Fig. S7A)].…”
Section: Discussionmentioning
confidence: 75%
“…For example, analyses of binding between AgamOBP1 and DEET showed that larger aromatic groups (e.g., indole or naphthalene ring) could be accommodated, and have π–π interactions with Trp114, resulting in the finding that 4‐methyl‐1‐(1‐oxodecyl)‐piperidine (modified from DEET) had stronger binding ability with AgamOBP1 54 . In another study, adding a hydrophilic group to a particular position of 1‐dodecanol could facilitate its interaction with Cydia pomonella pheromone binding protein 2, thus providing a foundation for development of biologically more active compounds 55 . Similarly, based on analyses of structural dynamics in our study, it is likely to enhance hydrogen bonding with Trp106 through adding hydrogen bond acceptor groups to geranyl formate [e.g., addition of ‐OH gives ( E )‐3,7‐dimethylocta‐2,6‐dien‐1‐yl hydrogen carbonate (Supporting Information, Fig.…”
Section: Discussionmentioning
confidence: 99%